Mental health among healthcare workers during the prolonged COVID-19 pandemic: A cross-sectional survey in Jilin Province in China - Ning, Liangwen; Jia, Huanhuan; Yu, Jianxing; Gao, Shang; Shang, Panpan; Cao, Peng; Yu, Xihe (Frontiers in Public Health, 2022)
Background: The prolonged COVID-19 pandemic has seriously impacted the mental health of healthcare workers. This study aimed to explore the mental health status of healthcare workers, compare the differences in mental health between physicians and nurses, and verify the impact of risk perception on mental health in the long-term COVID-19 pandemic in Jilin Province, China. Methods: A stratified random sample was used to conduct an on-site questionnaire survey in December 2020 to measure the mental health status, risk perceptions, and demographic characteristics of healthcare workers in Jilin Province, China. A total of 3,383 participants completed the questionnaire survey, of which 3,373 were valid questionnaires. Results: A total of 23.6% (n=795) of participants had symptoms of depression, 27.4% (n=923) had symptoms of anxiety, and 16.3% (n=551) had symptoms of stress. Physicians reported significantly higher rates of depression and anxiety than nurses (p=0.023, p=0.013, respectively). There was no significant difference in the proportion of participants with stress between physicians and nurses (p=0.474). Multivariate logistic regression results showed that healthcare workers who had a high level of risk perception were more likely to have symptoms of depression (AOR=4.12, p<0.001), anxiety (AOR=3.68, p<0.001), and stress (AOR=4.45, p<0.001) after controlling for other variables. Conclusions: At least one in six healthcare workers experienced mental health problems, and physicians were more likely than nurses to suffer from depression during the prolonged COVID-19 epidemic. Risk perception was highly predictive of depression, anxiety, and stress symptoms in medical staff. Public health interventions are needed to mitigate the long-term psychological impact of the COVID-19 pandemic.